Edukasi Potensi Radikalisme di Daerah Serta Pencegahan Pada Kalangan Pelajar di Kota Banjarmasin - Adwin Tista; Muhammad Ghazali Rahman; Hanafi H (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
The issue of the state of Radicalism and Terrorism in Indonesia is currently one of national threats. Radical ideologies continue to erode the nationalism of this nation. Radicalism being the embryo birth of the crime of Terrorism, Where the ideology can easily influence the civil society in Indonesia through social media to become perpetrators of terror that can endanger the rest of society. Programs of deradicalization through strengthening Character education of school students can be one of the soft power alternatives in rejecting radical ideologies. Through this character strengthening program students can be directed to prevent early on radical attitudes and understandings. Therefore, it takes dedication to the community to reject radicalism and terrorism through strengthening the character of school students in SMAN 3 Banjarmasin. This devotion is carried out using elements of active, creative, effective and fun education. Presentation of material using dialogue conversational methods and character-based question and answer. Using approach methods social jurisprudence (socio-legal) approach and using interdisciplinary or hybrid approach between normative aspects with sociological approach and using qualitative analysis i.e. by analyzing a data in depth and holistically. Then the expected result of this activity is Understanding and prevention regarding Education Potential Radicalism In The Area As well as Prevention Among Students In Banjarmasin City.